Nutritional approaches for managing obesity-associated metabolic diseases. Issue 3 (June 2017) - Botchlett, Rachel; Woo, Shih-Lung; Liu, Mengyang; Pei, Ya; Guo, Xin; Li, Honggui; Wu, Chaodong
Abstract : Obesity is an ongoing pandemic and serves as a causal factor of a wide spectrum of metabolic diseases including diabetes, fatty liver disease, and cardiovascular disease. Much evidence has demonstrated that nutrient overload/overnutrition initiates or exacerbates inflammatory responses in tissues/organs involved in the regulation of systemic metabolic homeostasis. This obesity-associated inflammation is usually at a low-grade and viewed as metabolic inflammation. When it exists continuously, inflammation inappropriately alters metabolic pathways and impairs insulin signaling cascades in peripheral tissues/organs such as adipose tissue, the liver and skeletal muscles, resulting in local fat deposition and insulin resistance and systemic metabolic dysregulation. In addition, inflammatory mediators, e.g., proinflammatory cytokines, and excessive nutrients, e.g., glucose and fatty acids, act together to aggravate local insulin resistance and form a vicious cycle to further disturb the local metabolic pathways and exacerbate systemic metabolic dysregulation. Owing to the critical role of nutrient metabolism in controlling the initiation and progression of inflammation and insulin resistance, nutritional approaches have been implicated as effective tools for managing obesity and obesity-associated metabolic diseases. Based on the mounting evidence generated from both basic and clinical research, nutritional approaches are commonly used for suppressing inflammation, improving insulin sensitivity, and/or decreasing fat deposition. Consequently, the combined effects are responsible for improvement of systemic insulin sensitivity and metabolic homeostasis.